Efficiency of technological methods of cultivation of sunflower maternal line - Alexander S. Bushnev; Gennady I. Orekhov; Irina A. Kotlyarova; Dina A. Kurilova; Yulia V. Mamyrko (Аграрная наука Евро-Северо-Востока, 2025)
The article presents the results of research on the effect of technological methods (seeding rates, macro- and microfertilizers, chemical and biological plant protection) on the growth and development, productivity elements, disease affection, seed germination and quality of seed material of the sunflower maternal line VK1-klp, as well as on the changes in the qualitative and quantitative composition of microbiota in the rhizosphere of sunflower. The research was conducted in 2023-2024 in the conditions of the Krasnodar region on ordinary and leached chernozems. Disease recording was carried out at sunflower stages BBCH 51 and BBCH 85 (according to the international BBCH-scale) in accordance with generally accepted methods of phytopathological research. Mycological analysis of soil samples (by the method of sequential soil dilution by A. I. Netrusov, identification of micromycetes in sunflower rhizosphere by M. A. Litvinov and A. Ya. Semenov (et al.)) was carried out before sowing and at the onset of the physiological maturity stage of the crop (soil sampling in the rhizosphere). The samples were counted and analyzed according to the methodology of V. S. Pustovoit All-Russian Research Institute of Oil Crops. It was established that agrotechnical methods had no effect on the mycological composition of the sunflower rhizosphere, contributed to the decrease of plant affection and positively influenced the growth and productivity of the crop. The application of fertilizers and chemical plant protection against diseases contributed to a 10 % decrease in the prevalence of sunflower dry rot (Rizopus spp.), an increase in plant height by 8.1 cm and the achievement of a high yield – 1.25 t/ha. Decreasing the seeding rate from 75 to 65 thousand pcs/ha resulted in a significant increase in the thousand-seed weight from 53.6 to 57.3 g. The best laboratory germination of seeds (98.0 %) was obtained with the combined use of biological plant protection and microfertilizers, field germination (95.4 %) – with the use of fertilizers and chemical plant protection. The results of the research can be the basis for the preparation of recommendations for increasing the production of seed material of maternal lines of sunflower with improved quality.